The pedagogical coordinator in public policies on education in Brazil (Olhar de Professor, 2023)
This article presents an investigation on public policies aimed at professionals working in pedagogical coordination in Brazil and seeks to analyze, among other aspects, public policies that refer, directly or indirectly, to the work of professionals working in coordination, from the idea from labor to current legislation. As a tool, documentary research was used and the results demonstrate that, despite some achievements in current legislation, such as the guarantee of PSPN in the Law on the Floor, there is much to be done in terms of public policies and the work of pedagogical coordination., because what is observed in the analysis of legislation, throughout the history of Brazil, is an imprecision and lack of clarity regarding the work of this professional, starting with the very name of the function, which has numerous nomenclatures and attributions in different entities federated.
Keywords: Pedagogical coordinator. Brazilian education. Public policy.